Correction: 24 Hours in the Life of HIV-1 in a T Cell Line. - Pejman Mohammadi; Sébastien Desfarges; István Bartha; Beda Joos; Nadine Zangger; Miguel Muñoz; Huldrych F Günthard; Niko Beerenwinkel; Amalio Telenti; Angela Ciuffi (PLoS Pathogens, 2015)
[This corrects the article DOI: 10.1371/journal.ppat.1003161.].